Polymorphisms in MTNR1A (rs2119882) and CLOCK (rs1801260) genes are associated with facial acne susceptibility in gas station workers - Yi Chi; Xueqin Yang; Donglin Deng; Peimao Li; Yingbiao Zhang (PLoS ONE, 2025)
This study aimed to explore the relationship between circadian rhythm gene polymorphisms, specifically MTNR1A rs2119882 and CLOCK rs1801260, and the risk of acne in an occupational population. MTNR1A encodes a melatonin receptor involved in circadian rhythm regulation, while CLOCK is a core transcription factor in the molecular circadian clock. Both genes are essential in maintaining hormonal balance, sleep-wake cycles, and inflammatory responses—factors closely associated with acne pathogenesis. A case-control study was conducted among 90 participants, comprising acne-affected workers (AAG), acne-free workers (AFG), and healthy control group (HCG). Peripheral blood samples were collected, and DNA was extracted for genotyping of MTNR1A rs2119882 and CLOCK rs1801260 polymorphisms. Sociodemographic, lifestyle, and occupational data were obtained via structured interviews. Logistic regression models were used to assess the association between gene polymorphisms and acne risk, adjusting for relevant covariates. Sensitivity analyses were performed to evaluate the robustness of the findings. In the overall population, no significant association was found between MTNR1A rs2119882 polymorphisms and acne risk. However, CLOCK rs1801260 polymorphisms showed a strong association with acne susceptibility. Under the dominant model, participants carrying the AG/GG genotypes exhibited a significantly higher risk of developing acne compared to those with the AA genotype (unadjusted odds ratios (OR) = 3.79, 95% CI: 1.27–11.31; adjusted OR = 5.08, 95% CI: 1.41–18.33). In the additive model, the risk of acne increased with additional G alleles (unadjusted OR = 2.95, 95% CI: 1.22–7.13; adjusted OR = 3.51, 95% CI: 1.25–9.81). Subgroup analysis among night shift workers revealed a significant association between MTNR1A rs2119882 and acne risk, such that carriers of the CC genotype exhibited increased susceptibility (adjusted OR = 3.97, p = 0.049). Moreover, individuals with AG/GG genotypes at CLOCK rs1801260 showed an even higher risk (OR = 4.96, 95% CI: 1.22–20.14). This study suggests that circadian rhythm gene polymorphisms, particularly CLOCK rs1801260, are associated with acne risk, especially in individuals working rotating night shifts.